2021
DOI: 10.24095/hpcdp.41.5.02
|View full text |Cite
|
Sign up to set email alerts
|

Substance use classes and symptoms of anxiety and depression among Canadian secondary school students

Abstract: Introduction Few studies have assessed patterns of substance use among Canadian adolescents. This cross-sectional study examined substance use classes among Canadian secondary school students and associations with anxiety and depression. Methods This study used data from Year 6 (2017/18) of the COMPASS study. Students (n = 51 767) reported their substance use (alcohol, cannabis, cigarette and e-cigarette use) and anxiety and depression symptoms. We employed latent cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 65 publications
3
14
1
Order By: Relevance
“…In contrast to our findings in the full sample, among students who used substances each year, we identified uni-directional effects with poly-substance being associated with increased anxiety in female students and increased anxiety and depression in male students from Wave 2 to Wave 3. Exploratory analysis from Wave 2 to Wave 3 (Supplementary Table 8, http://links.lww.com/CJA/A18) found that cigarette use may be partly driving this association, although it is important to note that previous research has also found an association between poly-use of alcohol and e-cigarettes and anxiety and depression 2 . These results are in part consistent with previous longitudinal research 13,14 .…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In contrast to our findings in the full sample, among students who used substances each year, we identified uni-directional effects with poly-substance being associated with increased anxiety in female students and increased anxiety and depression in male students from Wave 2 to Wave 3. Exploratory analysis from Wave 2 to Wave 3 (Supplementary Table 8, http://links.lww.com/CJA/A18) found that cigarette use may be partly driving this association, although it is important to note that previous research has also found an association between poly-use of alcohol and e-cigarettes and anxiety and depression 2 . These results are in part consistent with previous longitudinal research 13,14 .…”
Section: Discussionsupporting
confidence: 84%
“…[5][6][7][8][9] For instance, poly-substance use has been associated with elevated symptoms of depression and anxiety among adolescents aged 11 to 18 in crosssectional studies. 2,10 However, among studies that have examined depression symptoms at baseline and poly-substance use at follow-up, none have identified significant effects after controlling for covariates. 11,12 A small cohort study examined the effect in the opposite direction and identified that youth that used the highest number of substances had the highest depression scores at followup, although this study did not control for covariates.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations